Spatial distribution of particulate matter on winter nights in Temuco, Chile: Studying the impact of residential wood-burning using mobile monitoring. (1st October 2022) - Blanco, Estela; Rubilar, Francisco; Quinteros, Maria Elisa; Cayupi, Karen; Ayala, Salvador; Lu, Siyao; Jimenez, Raquel B.; Cárdenas, Juan Pablo; Blazquez, Carola A.; Delgado-Saborit, Juana Maria; Harrison, Roy M.; Ruiz-Rudolph, Pablo
Abstract: Temuco, a medium-sized city in the south of Chile, is heavily impacted by residential wood-burning particularly in winter, which causes strong episodes of air pollution. We spatially characterized the distribution of particulate matter (PM) during winter nights in Temuco using mobile measurements. In winter 2016 (June 8-July 15th), continuous monitors for PM ≤ 2.5 μm (PM2.5 ) and ultrafine particles <0.1 μm (UFP) were deployed in a vehicle along with a positioning system during 20 nights (20:00 to 2:00) in assigned routes that crossed the city and additional sampling was conducted at a central site. Measurements were expressed as concentrations and ratios to central site concentrations and collapsed by spatial grids of 50, 100, 200, and 400 m. Average PM2.5 concentrations were ∼100 μg m −3, while UFP ∼30, 000 counts cm −3 . Some neighborhoods had concentrations of PM2.5 nearly double those measured at a centrally located site, while other neighborhoods had less than half the measured level. We identified hotspots and cold spots of PM2.5 and UFP throughout the urban area—and observed some neighborhoods in which over 20% of the area was categorized as a hotspot for one of the pollutants (14 for PM2.5 and 11 for UFP out of 34). Using mobile monitoring—a relatively simple and inexpensive methodology— we characterized the spatial distribution of pollutants and likely clusters for the time period, which may guide future spatial campaigns and help targeting local interventions aimed at air pollution mitigation. Graphical abstract: Image 1 Highlights: Air pollution due to wood-burning is a growing concern around the world. Cities in Southern Chile have massive emissions due to residential wood-burning. Mapping of concentrations was conducted by an innovative mobile method. Mobile monitoring identified spatial variations in particulate matter. We identified clusters of spatially correlated hotspots of particulate matter.